9G4+ Autoantibodies Are an Important Source of Apoptotic Cell Reactivity Associated With High Levels of Disease Activity in Systemic Lupus Erythematosus. Issue 12 (December 2013) - Jenks, Scott A.; Palmer, Elise M.; Marin, Elides Y.; Hartson, Louise; Chida, Asiya Seema; Richardson, Christopher; Sanz, Ignacio
<x xml:space="preserve">Abstract</x> Objective To determine the prevalence of anti–apoptotic cell (anti‐AC) antibodies with the 9G4 idiotype (9G4+) and the relationship between this and other known 9G4+ specificities and disease activity in patients with systemic lupus erythematosus (SLE). Methods Serum samples from 60 SLE patients and 40 healthy donors were incubated with apoptotic Jurkat cells and assayed by flow cytometry for the binding of 9G4+ antibodies. The samples were also tested for 9G4+ reactivity against naive B cells and total IgG and IgM anti‐AC antibody reactivity. Results The 9G4+ antibodies bound late ACs in sera from a majority of the SLE patients (60%) but in sera from only 2 healthy control subjects. Among samples with global IgM or IgG anti‐AC antibodies, those with 9G4+ anti‐AC antibodies predominated. Patients with high levels of 9G4+ anti‐AC antibodies were more likely to have active disease. This was the case even in patients with IgG anti‐AC antibodies or anti–double‐stranded DNA antibodies. Patients with lupus nephritis were also more likely to have 9G4+ anti‐AC antibodies. While 9G4+ reactivity to ACs often coincided with anti–B cell reactivity, some samples had distinct anti–AC or anti–B cell reactivity. Conclusion The 9G4+ antibody represents a major species of anti‐AC antibody in SLE serum, and this autoreactivity is associated with disease activity. The anti‐AC reactivity of 9G4+ antibodies can be separated from the germline VH4–34–encoded anti–B cell autoreactivity. Our results indicate that ACs are an important antigenic source in SLE that positively selects B cells with intrinsic autoreactivity against other self antigens. This selection of 9G4+ B cells by ACs may represent an important step in disease progression.